2020
DOI: 10.1589/rika.35.229
|View full text |Cite
|
Sign up to set email alerts
|

Factors Inhibiting Home Return of Stroke Patients Living Alone

Abstract: To clarify the factors inhibiting home return of stroke patients living alone. [Participants and Methods] The subjects were 97 stroke patients who were living alone. We conducted hierarchical cluster analysis with variables of outcome, admission Functional Independence Measure (FIM), age, and inpatient days in order to identify groups having difficulty adjusting to discharge, and made comparisons among the groups. We conducted a text mining analysis after investigating the causes of difficulty in adjusting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In fact, studies by Morita et al 38) and Asakawa et al 3) have also highlighted the importance of understanding the patient's living environment before discharge and planning appropriate support. Thus, in addition to the report by Sawamura et al 17) , many other studies have revealed social problems of stroke patients that are similar to the social score established in this study. Therefore, the social score in this study was considered to have some validity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In fact, studies by Morita et al 38) and Asakawa et al 3) have also highlighted the importance of understanding the patient's living environment before discharge and planning appropriate support. Thus, in addition to the report by Sawamura et al 17) , many other studies have revealed social problems of stroke patients that are similar to the social score established in this study. Therefore, the social score in this study was considered to have some validity.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been reported that not only ADL ability but also social factors such as family structure 1 , 2 , 3 , 4 , 5 , 29 ) , economic issues 30 , 31 , 32 ) , and coordination of social resources such as long-term care insurance services and the community 33 , 34 , 35 ) are involved in the return home of stroke patients. Sawamura et al 17 ) found that the following factors inhibited the return to living alone of stroke patients who had lived alone before the illness: patient’s abilities such as higher brain dysfunction, motor paralysis, and ADL ability; human resources such as family and supporters; financial problems; adjustment of long-term care insurance; difference between the patient’s wishes and reality. Based on this report, we defined social score using five items: (1) absence of a key person, (2) absence of a neighborhood supporter, (3) financial problems, (4) receipt of public assistance, and (5) difficulty in coordinating long-term care insurance services upon discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations